Protection of Mice from Acute Graft-versus-Host Disease Requires CD28 Co-stimulation on Donor CD4+ Foxp3+ Regulatory T Cells - Uri, Anna; Werner, Sandra; Lühder, Fred; Hünig, Thomas; Kerkau, Thomas; Beyersdorf, Niklas (Frontiers in Immunology, 2017)
Acute graft versus host disease (aGvHD) is a major cause of morbidity and mortality after allogeneic hematopoietic stem cell plus T cell transplantation (allo-HSCT). In this study, we investigated the requirement for CD28 co-stimulation of donor CD4+ conventional (CD4+CD25-Foxp3-, Tconv) and regulatory (CD4+CD25+Foxp3+, Treg) T cells in aGvHD using Tamoxifen-inducible CD28 knock-out (iCD28KO) or wild-type (wt) littermates as donors of CD4+ Tconv and Treg. In the highly inflammatory C57BL/6 into BALB/c allo-HSCT transplantation model, CD28 depletion on donor CD4+ Tconv reduced clinical signs of aGvHD, but did not significantly prolong survival of the recipient mice. Selective depletion of CD28 on donor Treg did not abrogate protection of recipient mice from aGvHD until about day 20 after allo-HSCT. Later, however, the pool of CD28-depleted Treg drastically declined as compared to wt Treg. Consequently only wt, but not CD28-deficient, Treg were able to continuously suppress aGvHD and induce long-term survival of the recipient mice. To our knowledge, this is the first study that specifically evaluates the impact of CD28 expression on donor Treg in aGvHD. Moreover, the delayed kinetics of aGvHD lethality after transplantation of iCD28KO Treg provides a novel animal model for similar disease courses found in patients after allo-HSCT.